PROBLEMS OF FORMING A HEALTHY LIFESTYLE AMONG YOUTH (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
In this article, the fight against drug-related crimes is carried out not only with the application of criminal legal norms, but also with the use of mass media and administrative legal norms, in this regard, especially "Family and Society" It is justified that the development of educational programs among minors is one of the main tasks of the team of the institute.